Pengaruh Pertumbuhan Ekonomi, Inflasi dan Suku Bunga Terhadap Investasi di Provinsi Jambi - Razali Razali (Science of Management and Students Research Journal (SMS), 2019)
This study shows how much influence economic growth, inflation and interest rates on investment in Jambi Province. Used include data Economic Growth, Inflation, Interest Rates and Investment from 2000 to 2018.Based on the results of SPSS calculations, the authors have an influence on investment in Jambi Province because of F count (0.300)> F table (4.12) then ho is rejected or different from zero. This means that all regression coefficients or economic growth, inflation and interest rates together have the same effect on investment in Jambi Province.From the results of the analysis in this study, it can be concluded, together with the variables of economic growth, inflation and interest rates affect investment. Individually, the variable economic growth, inflation and interest rates can affect investment, which has the greatest influence on investment in Jambi Province.